2017
DOI: 10.1124/mol.116.107839
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of G Protein-Coupled Receptors: From the Barcode Hypothesis to the Flute Model

Abstract: Seven transmembrane G protein-coupled receptors (GPCRs) are often phosphorylated at the C terminus and on intracellular loops in response to various extracellular stimuli. Phosphorylation of GPCRs by GPCR kinases and certain other kinases can promote the recruitment of arrestin molecules. The arrestins critically regulate GPCR functions not only by mediating receptor desensitization and internalization, but also by redirecting signaling to G protein-independent pathways via interactions with numerous downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 110 publications
(114 reference statements)
0
90
0
Order By: Relevance
“…Of the 389 receptors without codes in their tails, 308 (~79%) were found to belong to the olfactory receptor family, which has been shown to recruit arrestin through phosphorylation sites within their ICL3 just N-terminal to TM6 (Mashukova et al, 2006). Analysis of the remaining 81 receptors found that 48 contained full or partial codes within their ICL3 and comprised many members from the serotonin, dopamine, muscarinic, and α-adrenergic families, which have been shown to recruit β-arrestins in a ICL3-dependent manner (Smith and Rajagopal, 2016; Yang et al, 2017). In total, our phosphorylation code analysis accounts for 96% of the GPCR proteome.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 389 receptors without codes in their tails, 308 (~79%) were found to belong to the olfactory receptor family, which has been shown to recruit arrestin through phosphorylation sites within their ICL3 just N-terminal to TM6 (Mashukova et al, 2006). Analysis of the remaining 81 receptors found that 48 contained full or partial codes within their ICL3 and comprised many members from the serotonin, dopamine, muscarinic, and α-adrenergic families, which have been shown to recruit β-arrestins in a ICL3-dependent manner (Smith and Rajagopal, 2016; Yang et al, 2017). In total, our phosphorylation code analysis accounts for 96% of the GPCR proteome.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the distinct GPCR phosphorylation profiles that result from the actions of different kinases are responsible for various signaling outcomes. This concept is known as the "phosphorylation barcode" and is critical for the multidimensional features of GPCR signaling (3)(4)(5)(6)(43)(44)(45). Thus, the precise analysis of BLT1 phosphorylation is important to clarify the biological functions of this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of seven transmembrane (7TM) GPCRs is a regulatory mechanism to modulate G protein signaling . In animals, extracellular signals induce GPCR phosphorylation by G protein–coupled receptor kinases (GRKs) on the C‐terminus and intracellular loops leading to arrestin recruitment and signal desensitization through receptor endocytosis.…”
Section: Atgpa1 Rlks Used In This Studymentioning
confidence: 99%
“…In animals, extracellular signals induce GPCR phosphorylation by G protein–coupled receptor kinases (GRKs) on the C‐terminus and intracellular loops leading to arrestin recruitment and signal desensitization through receptor endocytosis. Phosphorylation patterns of GPCR are recognized by arrestins via a phospho‐barcoding mechanism to activate arrestin‐dependent effectors in diverse cellular processes . In Arabidopsis thaliana , AtGPA1 is kept in its deactivated state by a 7TM GAP (AtRGS1) and the ligand‐induced phosphorylation and endocytosis of AtRGS1 activates AtGPA1 via de‐repression …”
Section: Atgpa1 Rlks Used In This Studymentioning
confidence: 99%